Ce3+-Doped garnet phosphors: composition modification, luminescence properties and applications. (11th November 2016) - Xia, Zhiguo; Meijerink, Andries
Abstract : Crystal chemistry, luminescence and applications of Ce 3+ -doped garnets are reviewed and the tuning of optical properties is explained via combined insights from experiments and theory. Abstract : Garnets have the general formula of A3 B2 C3 O12 and form a wide range of inorganic compounds, occurring both naturally (gemstones) and synthetically. Their physical and chemical properties are closely related to the structure and composition. In particular, Ce 3+ -doped garnet phosphors have a long history and are widely applied, ranging from flying spot cameras, lasers and phosphors in fluorescent tubes to more recent applications in white light LEDs, as afterglow materials and scintillators for medical imaging. Garnet phosphors are unique in their tunability of the luminescence properties through variations in the A, [B] and (C) cation sublattice. The flexibility in phosphor composition and the tunable luminescence properties rely on design and synthesis strategies for new garnet compositions with tailor-made luminescence properties. It is the aim of this review to discuss the variation in luminescence properties of Ce 3+ -doped garnet materials in relation to the applications. This review will provide insight into the relation between crystal chemistry and luminescence for the important class of Ce 3+ -doped garnet phosphors. It will summarize previous research on the structural design and optical properties of garnet phosphors and also discuss future research opportunities in this field.